2006
DOI: 10.1111/j.1540-8167.2006.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Marshall Vein as Arrhythmogenic Source in Patients with Atrial Fibrillation: Correlation Between its Anatomy and Electrophysiological Findings

Abstract: To determine VOM anatomy is important to identify non-PV foci around the ends of VOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 32 publications
(61 reference statements)
3
67
1
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30] However, in the present series, exclusion of the LA posterior wall had no effect on the incidence of AF recurrences after CPVA. It should be noted that a larger area of posterior venous-atrial tissue was excluded when PV encirclement was performed in this study as compared with procedures in which PVs are ablated at their ostia.…”
Section: Discussioncontrasting
confidence: 48%
“…[22][23][24][25][26][27][28][29][30] However, in the present series, exclusion of the LA posterior wall had no effect on the incidence of AF recurrences after CPVA. It should be noted that a larger area of posterior venous-atrial tissue was excluded when PV encirclement was performed in this study as compared with procedures in which PVs are ablated at their ostia.…”
Section: Discussioncontrasting
confidence: 48%
“…3,25 The relationship between the precise ISP dose and arrhythmogenic inducibility remains unknown; however, the majority of PV/non-PV foci may be revealed during a high dose isoproterenol administration of up to 20 g/min or after cardioversion of AF. 2,26 High-dose ISP often invokes vagally mediated nerve reflex bradycardia, which appears to cause an increased arrhythmogenicity due to autonomic nerve competition.…”
Section: Induction Of Arrhythmogenic Focimentioning
confidence: 99%
“…However, neither of the studies considered PV isolation as a procedural endpoint for CPVA, namely CPVI which many studies have shown results in higher efficacy for CPVI in the treatment of AF. [11][12][13][14][15] Moreover, both those studies used conventional SPVI to isolate the PVs. Compared with them, 3,5 the present study has 2 different features: (1) PV isolation, rather than voltage abatement, was the primary endpoint of CPVI and (2) after systemic SPVI, we performed additional LA linear ablation for patients with sustained or inducible AF.…”
Section: Previous Studiesmentioning
confidence: 99%
“…[11][12][13] CPVI approach is designed to produce 2 circular lesion sets along the PV antrum, with the endpoint of PV isolation. As demonstrated by Ouyang et al, 9 CPVI alone (without additional LA linear lesions) is very effective in treating PAF, but the approach also has some demerits because of the nature of a predetermined anatomic lesion set.…”
Section: Ablation Approachesmentioning
confidence: 99%
See 1 more Smart Citation